The Beneficial Properties of Virgin Coconut Oil in Management of Atopic Dermatitis - Chew, Yik‑Ling (Pharmacognosy Reviews)
Atopic dermatitis (AD) is a chronic, inflammatory skin disease that is characterized by intense pruritus and eczematous lesions. It is an increasingly pruritic inflammatory skin disorder which can affect both children and adults. Natural products offer great hope in the identification of bioactive lead compounds and their development into topical cream or ointment in managing skin diseases which are associated with inflammatory response. One of the most popular natural products which have been vastly used in managing AD is virgin coconut oil (VCO). VCO is extracted from the fresh and mature kernel of the coconut (Cocos nucifera L.) through wet and dry methods, without altering the valuable phytochemicals and physiochemical properties of the oil. It possesses numerous health benefits from the retained physiochemical properties from its triglycerides and medium chain fatty acids. The use of VCO in the management of AD is one of the topical therapies which have been proven to have good therapeutic effects and it is safe for topical applications. Studies have been proven that VCO exhibits antioxidant, anti‑inflammatory, antibacterial, wound healing, and moisturizing properties which were extremely important in the management of AD.
Keywords: Anti‑inflammatory; antioxidant; lauric acid; moisturizer; virgin coconut oil; wound healing